Children of parents with a mental illness – stigma questionnaire: validation and revision - Stracke, Markus; Dobener, Lisa-Marie; Christiansen, Hanna (Frontiers in Psychiatry, 2024)
Introduction: Mental disorders are often stigmatized in society. The stigma of mental illness affects people with a mental illness themselves as well as their family members – a phenomenon called stigma by association (SBA). Children of parents with a mental illness (COPMI) are a particular vulnerable group for SBA. In our systematic review, experienced SBA, anticipated SBA, affiliate SBA and structural discrimination were identified as relevant stigma dimensions for COPMI. To assess SBA in adolescent COPMI, the COPMI-SQ was developed. Methods: N = 930 adolescents completed the study. Of those, N = 380 adolescents reported growing up with at least one parent with a mental illness. Using confirmatory (CFA) and exploratory factor analyses (EFA) as well as standard item and reliability analyses, we analyzed and revised the COPMI-SQ in the first sample. To validate the factorial structure of the revised COPMI-SQ, CFA was also conducted in the independent sample of the other N = 550 adolescents who reported not growing up with a parent with a mental illness (sample 2). Results: CFA in sample 1 resulted in an inadequate model fit for the theoretically assumed four factor structure. Following EFA, item and reliability analyses in sample 1, the COPMI-SQ was reduced to four scales (“Experienced SBA”, “Affiliate SBA”, “Shame” and “Anticipated SBA”) and two additional screening scales (“Health care” and “Social support”). To facilitate questionnaire use, only the three best items were retained in each scale, reducing the total item number to 12 plus five additional screener items. Internal consistency was found to be good for the total scale and almost acceptable to good for the subscales . CFA in sample 2 also resulted in an inadequate model fit for the theoretically assumed for factor structure. In comparison, the final version of the COPMI-SQ-r showed the best model fit. Discussion: The revised version of the COPMI-SQ (COPMI-SQ-r) is a reliable and economic questionnaire to assess SBA in adolescents who grow up with a parent with a mental illness. The COPMI-SQ-r can be used to help develop and evaluate anti-stigma and general interventions foraffected adolescents.